Patients' and clinicians' experiences of holistic needs assessment using a cancer distress thermometer and problem list: A qualitative study. (August 2016) - Biddle, Lucy; Paramasivan, Sangeetha; Harris, Susan; Campbell, Rona; Brennan, James; Hollingworth, William
Abstract: Purpose: Psychosocial needs assessment is recommended for patients undergoing cancer treatment, but trials of effectiveness of assessment tools provide mixed results. This qualitative study aimed to understand how such tools are experienced by patients and clinicians in order to optimise use in the future. Methods: Qualitative interviews were used in a mixed-methods sequential design following a randomised controlled trial of needs assessment using the Distress Thermometer and Problem List (DT&PL), and explored patients' and clinicians' evaluations of the needs assessment process. Results: Benefits of needs assessment using the DT&PL included the potential to detect hidden distress, allow opportunity for distress to be discussed, and to deliver outcomes to address problems. However, effectiveness and patient willingness to report all forms of distress could be hindered by: clinicians feeling ill-equipped to deal with 'non-physical' distress and patients questioning their appropriateness to do so; time constraints; insufficient support services and referral guidelines; inappropriate timing; and lack of follow-up. Conclusions: The benefits of a holistic needs assessment cannot be realised without matching time and frequency of administration to the dynamic nature of distress during cancer, and making changes to the context of delivery – for instance, providing protected time, increasing referral options and clinician training. Significant investment is needed to optimise potential benefits for patients. Highlights: Patients and clinicians evaluated using the distress thermometer to assess need. Most clinicians reported feeling ill-equipped to deal with psychosocial distress. Time constraints and uncertainty about where to refer were barriers for clinicians. Timing and frequency of administration emerged as fundamental to success. Benefits of needs assessment are contingent upon the process and context of delivery.